Energy poverty alleviation and climate change mitigation: Is there a trade off? - Shoibal Chakravarty; Massimo Tavoni (Fondazione Eni Enrico Mattei (FEEM), 2013)
Energy poverty alleviation has become an important political issue in the most recent years. Several initiatives and policies have been proposed to deal with poor access to modern sources of energy in many developing countries. Given the large number of people lacking basic energy services, an important question is whether providing universal access to modern energy could significantly increase CO2 emissions. This paper provides one of the few formal assessments of this problem by means of a simple but robust model of current and future energy consumption. The model allows mapping energy consumption globally for different classes of energy use, quantifying current and future imbalances in the distribution of energy consumption. Our results indicate that an energy poverty eradication policy to be met by 2030 would increase global final energy consumption by about 7% (or 19EJ). This is the same quantity of energy which would be added between now and 2030 by individuals with energy consumption above current European standards. The additional energy infrastructure needed to eradicate energy poverty would produce 16-131 GtCO2 over the 21st century and contribute at most 0.1C of additional warming.
Keywords: Q43; Q54; 330; Energy Poverty; Climate Change; Household Energy Consumption